Breast carcinoma grading, estimation of tumor size, axillary lymph node status, staging, and nottingham prognostic index scoring on mastectomy specimens - Ahmad Zubair; Khurshid Amna; Qureshi Asim; Idress Romana; Asghar Nasira; Kayani Naila (Wolters Kluwer Medknow Publications, 2009)
Introduction: Breast carcinoma is the most common malignant tumor and the leading cause of cancer death in women. In western countries, a sharp increase in the detection of breast carcinoma, largely due to widespread use of mammography, has recently led to a fall in breast cancer mortality. This, however, is not true for less developed countries, in which mortality continues to rise. Objective: The aim of this study was to acquire information about the extent and spread of breast carcinoma in our patients by grading the tumors, determining the tumor size, and axillary lymph node status, staging of the tumors and Nottingham Prognostic Index (NPI) scoring on the available material. Materials and Methods: One hundred and twenty consecutive mastectomy specimens with axillary lymph node sampling removed for breast carcinoma and received in the section of histopathology, Aga Khan University, in the year 2005, were included in the study. Standard protocols were used for the processing of the specimens, and reporting was done using a standard format incorporating all relevant tumor parameters. NPI was applied to the cases. Results: Out of the 120 cases, 5 (4.17) were grade 1, 91 (75.83) were grade 2, and 24 (20%) were grade 3. Also, 9 cases (7.5%) were T1 (4 were T1b, and 5 were T1c); 53 (44.16%) were T2; 50 (41.66%) were T3; and 8 (6.66%) were T4. Axillary lymph nodes were available in 107 cases. In 13 cases, no lymph nodes were recovered. Out of 107 cases 27 (25.23%) lymph nodes were negative for metastases pN0; 29 (27.10%) cases were pN1; 26 (24.30) were pN2; and 25 cases (23.36%) were pN3. Extranodal spread was present in 56 (70%) out of the 80 cases in which lymph nodes were positive. The average microscopic size of nodal metastasis was 1.7 cms. Significant statistical association was found between the number of positive nodes and perinodal extension (P = 0.001). Tumor necrosis was present in 76 out of 120 cases (63.33%). Vascular invasion was present in 43 out of 120 cases (35.83%). NPI scores were greater than 5.4 in 60 out of 107 cases (56.1%) indicating poor prognosis. Conclusion: The large majority of the cases were grade 2 tumors. Most cases (all grades) were T2 or T3, and were axillary lymph node positive. Large majority of cases with nodel metastases showed extra nodal spread. The majority of patients had NPI scores greater than 5.4 indicating poor prognosis. Significant statistical association was found between the number of positive nodes and perinodal extension (P = 0.001). The findings show extensive and advanced disease trends in our patients.